Treatment of nonsyndromic dentigerous cysts in primary dentition - Mehmet Cemal Akay; Erdem Kaya; Mert Zeytinoğlu (Dove Medical Press, 2011)
Mehmet Cemal Akay, Erdem Kaya, Mert ZeytinoğluFaculty of Dentistry, Department of Oral and Maxillofacial Surgery, Ege University, Bornova, Izmir, TurkeyObjective: Dentigerous cysts are benign odontogenic cysts that are associated with the crowns of permanent teeth. They usually occur singly and are located in the mandible. Nonsyndromic bilateral dentigerous cysts (NSBDC) are rarely seen during childhood. The aim of this study was to determine the long-term effects of the marsupialization technique in growing children with NSBDC.Study design: Seven patients with NSBDC (4 female, 3 male) ranging in age from 7 to 9 years (mean 8.35 years) were involved in the study. All the individuals were treated by marsupialization. Space-maintaining appliances were applied during permanent teeth eruption. Intraoral photographs, and panoramic and periapical films were taken before surgery and during healing.Results: The NSBDC were successfully treated by the marsupialization technique and rapid healing period was observed in the growing patients, without any loss of permanent teeth. No recurrence was seen in the long-term follow-up period (3–10 years).Conclusion: Our clinical and radiological results revealed that using the marsupialization technique in children with NSBDC provided safe healing of permanent teeth around the dentigerous cysts in a short period. However, treatment planning and regular clinical follow-ups are necessary to ensure clinical success.Keywords: nonsyndromic bilateral dentigerous cysts, primary dentition, marsupialization